PiCO2 Monitoring of Transferred Jejunum Perfusion Using an Air Tonometry Technique After Hypopharyngeal Cancer Surgery. Issue 11 (March 2015) - Ozawa, Hiroyuki; Imanishi, Yorihisa; Ito, Fumihiro; Watanabe, Yoshihiro; Kato, Takashi; Nameki, Hideo; Isobe, Kiyoshi; Ogawa, Kaoru; Kapritsou., Maria
<x xml:space="preserve">Abstract</x> Abstract This study aimed to investigate the usefulness of intraluminal PCO2 (PiCO2) monitoring by air tonometry for the assessment of the vascular condition of the transferred jejunum after surgery for hypopharyngeal cancer. PiCO2 in the transplanted jejunum of 24 patients was monitored using air tonometry after radical surgery for hypopharyngeal cancer from 2003 to 2010. All but 1 patient, who removed the catheter before monitoring began, were monitored safely. PiCO2 in the transferred jejunum correlated with arterial PCO2 (PaCO2) that was measured concurrently, and dissociation of PiCO2 from PaCO2 was observed in cases with vascular complication. In those cases without postoperative vascular complication, the PiCO2 value gradually increased for 3 hours but then decreased by 12 hours after surgery. Three patients experienced major vascular complication. All 3 patients had continuous elevation of PiCO2 >100 mm Hg, although vascular flow in 1 patient recovered by removal of a venous thrombosis and reanastomosis of the vein 7.5 hours after surgery. Four other patients who experienced elevation of PiCO2 had their skin suture released for decompression of their neck wound, resulting in a decrease in PiCO2 after treatment. The current results demonstrated that continuous monitoring of PiCO2 by air tonometry accurately reflects the vascular condition of the transferred jejunum, and this method is one of the best options for postoperative monitoring of jejunum blood perfusion.